Who Will Be the Next President?: A Guide to the U.S. Presidential Election System - Belenky, Alexander S. (Springer Nature, 2016)
Private International Law, International & Foreign Law, Comparative Law; US Politics; Theories of Law, Philosophy of Law, Legal History; Electoral Politics; Mathematics in the Humanities and Social Sciences